Murder on the Marlow Belle : a novel - Thorogood, Robert (Thorogood, Robert. Marlow Murder Club mystery, 2025)
"Verity Beresford is worried about her husband. Oliver didn't come home last night, so of course Verity goes straight to Judith Potts, Marlow's resident amateur sleuth, for help. Oliver, founder of the Marlow Amateur Dramatic Society, had rented The Marlow Belle, a private pleasure cruiser, to host an exclusive party for the society, but no one remembers seeing him disembark. And when Oliver's body washes up on the Thames with two bullet holes in him, it's time for the Marlow Murder Club to leap into action. Oliver was, by all accounts, a rather complicated fellow, with a reputation for bullying children during nativity play rehearsals, and he wasn't short of enemies. Judith, Suzie, and Becks are convinced they'll find his killer in no time. But things are not as they seem in the Marlow Amateur Dramatic Society, and this case is not so clear-cut after all. The gang will need to keep their wits about them to solve this case... otherwise a killer will walk free." --